Hydatid Choleperitoneum. Hydatid cyst of quadrate Iobe of the liver. Biliary stricture - Davidenko, Nicolás; Curuchet, Eduardo; Davidenko, Antonio (Cirugía del Uruguay, 1979)
Report of a case of Hydatid Choleperitoneum with sub - acute evolution which presented, an enlarged abdomen with free ascitis and jaundice.